Predictors of Pulmonary Tuberculosis Prevention in Surabaya, Indonesia - Abdul Aziz Alimul Hidayat; Ratna Agustin; Siwi Sabdasih (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: Pulmonary tuberculosis (TB) continues to pose a critical public health challenge in Indonesia, characterized by high transmission rates, particularly within household settings. Despite extensive efforts to mitigate the spread of TB, persistent barriers such as low adherence to prevention and treatment protocols hinder progress. Identifying the factors that influence adherence is essential to optimizing the efficacy of intervention strategies. This study aims to investigate the key predictors influencing adherence to preventive measures for pulmonary TB transmission in Surabaya City. Methods: A quantitative research design employing a cross-sectional approach was utilized. Data were collected from 225 pulmonary TB patients attending community health centers in Surabaya City between September and December 2023. The variables examined included demographic characteristics, perceived benefits, barriers, susceptibility, severity, and self-efficacy. Statistical analysis was conducted using multiple logistic regression, with significance set at p<0.05. Results: Significant predictors of adherence included age (p=0.048; OR=0.413), gender (p=0.009; OR=0.328), socioeconomic status (p=0.033; OR=3.052), perceived benefits (p=0.009; OR=10.086), barriers (p=0.007; OR=0.704), and self-efficacy (p=0.005; OR=29.335). Patients aged above 45 years, those reporting higher perceived benefits, and those with greater self-efficacy demonstrated higher adherence to TB prevention measures. These findings underscore the importance of self-efficacy, perceived benefits, and socioeconomic factors as significant determinants of adherence. The study's contribution lies in its exploration of adherence predictors within a high-risk population, offering valuable insights to inform targeted public health interventions. Conclusion: Age, perceived benefits, barriers, and self-efficacy emerged as critical predictors of adherence to pulmonary TB prevention strategies in Surabaya City. Interventions aimed at strengthening self-efficacy and providing targeted educational programs for younger populations are recommended to enhance TB control efforts. Additionally, integrating these findings into broader public health frameworks, such as national TB control strategies, can amplify their impact and contribute to improved health outcomes.